Increasing Motivation to Learn Science through a Scientific Approach to Students of SDS Muhammadiyah 02 Medan - Anisa Rahmah; Alda Elfiyana Dwiyanti; Indah Pratiwi (Al'Adzkiya International of Education and Sosial (AIoES) Journal, 2023)
This study aims to increase the motivation to learn science in SDS Muhammadiyah 02 Medan students. This research is a class action research, with the subject of class II students at SDS Muhammadiyah 02 Medan, totaling 20 people. This research procedure consists of four stages, namely planning, implementation, observation and reflection. The data will be taken later through the process of observation and questionnaires. Data were analyzed with qualitative descriptions. In the results of the research later it can be seen that the process of students' motivation in learning science has increased. Where there were 15 students who were in good and very good criteria in the process of motivation to learn science at SDS Muhammadiyah 02 Medan.